Gastrointestinal digestion of hazelnut allergens on molecular level: Elucidation of degradation kinetics and resistant immunoactive peptides using mass spectrometry. Issue 10 (14th August 2017) - Korte, Robin; Bräcker, Julia; Brockmeyer, Jens
Abstract : Scope: Allergy to hazelnut seeds ranks among the most prevalent food allergies in Europe. The aim of this study was to elucidate the gastrointestinal digestion of hazelnut allergens on molecular level. Methods and results: Hazelnut flour was digested in vitro following the Infogest consensus model. For six allergenic proteins, the time‐dependent course of digestion was monitored by SDS‐PAGE and HPLC−MS/MS, and degradation products were characterized by a bottom‐up proteomics approach. Depending on the molecular structure, a specific biochemical fate was observed for each allergen, and degradation kinetics were traced back to the peptide level. 1183 peptides were characterized, including 130 peptides that carry known IgE‐binding epitopes and may represent sensitizers for hazelnut allergy. The kinetics of peptide formation and degradation were determined by label‐free quantification and follow a complex multi‐stage mechanism. Conclusion: We present a comprehensive survey on the gastrointestinal digestion of a relevant allergenic food on level of the peptidome, including the first systematic characterization and quantification of degradation products. This provides information on the differential resistance of plant food allergens and their structural elements undergoing digestion and forms the basis for a deeper understanding of the molecular principles responsible for sensitization to food allergy. Abstract : Sensitization to hazelnut allergens via the gastrointestinal tract has been associated with severe clinical symptoms. Therefore, the biochemical fate of six relevant hazelnut allergens undergoing digestion is studied in vitro. Product structures and digestion kinetics are elucidated by HPLC−MS/MS. 1183 digestion resistant peptides are characterized that may represent sensitizers or elicitors for hazelnut allergy, and a comprehensive insight into the molecular dynamics of the proteolytic degradation of plant food allergens is provided.